Does retraction after misconduct have an impact on citations? A pre–post study - Esteve Fernández; Alberto Ruano-Raviña; Cristina Candal-Pedreira; Jorge Ramos; Isabel Campos-Varela; Mónica Pérez-Ríos (BMJ Global Health, 2020)
Background Retracted articles continue to be cited after retraction, and this could have consequences for the scientific community and general population alike. This study was conducted to analyse the association of retraction on citations received by retracted papers due to misconduct using two-time frames: during a postretraction period equivalent to the time the article had been in print before retraction; and during the total postretraction period.Methods Quasiexperimental, pre–post evaluation study. A total of 304 retracted original articles and literature reviews indexed in MEDLINE fulfilled the inclusion criteria. Articles were required to have been published in a journal indexed in MEDLINE from January 2013 through December 2015 and been retracted between January 2014 and December 2016. The main outcome was the number of citations received before and after retraction. Results were broken down by journal quartile according to impact factor and the most cited papers during the preretraction period were specifically analysed.Results There was an increase in postretraction citations when compared with citations received preretraction. There were some exceptions however: first, citations received by articles published in first-quartile journals decreased immediately after retraction (p<0.05), only to increase again after some time had elapsed; and second, postretraction citations decreased significantly in the case of articles that had received many citations before their retraction (p<0.05).Conclusions The results indicate that retraction of articles has no association on citations in the long term, since the retracted articles continue to be cited, thus circumventing their retraction.